A Orquestra Ribeiro Bastos de São João del-Rey - MG: prática e aprendizagem musical em uma tradição tricentenária - Fabiola Moreira Resende (2011)
The main objective of this research was to contribute to a better understanding of the learning processes that occur within the eighteenth sacred musical orchestra "Orquestra Ribeiro Bastos" (ORB) - composed by choristers, string and wind instrumentalists - from São João del Rei, a town in Campos das Vertentes in Minas Gerais. In order to achieve the goal intended in this project, the methodological procedure which proved to be a better fit was the one known as mixed methods proposed by Creswell (2007). Data collection was done through participant observation, and also questionnaires semi-structured were applied, together with two interviews held with the conductor of the orchestra, Stella Maria Neves Valle. The music learning processes that will be discussed throughout this work had as a conductor the Situated Learning Theory by Lave and Wenger (1991), the proposal of the British music educator Lucy Green (1988, 1997, 2005, 2008), which seeks to understand musical meanings, and Arévalo's ideas (1998, 2004, 2010) on the concepts of "tradition, heritage and identity." Regarding historical and musicological aspects related to the musical practice within "Campos das Vertentes", the theoretical framework of the thesis was José Maria Neves (1987): The Orchestra Ribeiro Bastos and musical life in São João del Rei. This paper is divided in five parts, and includes a brief biography of composers cited throughout the dissertation, there is also a glossary containing terms regarding liturgical items encountered in the paper. In the first chapter, there is a clarification on the social and historical context in which the research was conducted, throughout this I included my main goals, motivations, the methodology and theoretical considerations. In the second chapter, it is told a brief history of the city of São João del Rei and the beginning of its musical tradition, in which it is developed a reflection upon the possible origins of the ORB, its social structure and the profile of its members today. The third chapter deals with a description of the daily activities of the Orchestra, the forms of action of its members and exposes the motivations that lead them to stay and engage in music learning process. In the fourth chapter, I present historical aspects of music education in Europe, Brazil and São João del Rei - to mid-twentieth century. I discuss the formative processes of the members of the ORB in the XXI century and describe the process through which the sacred repertoire composed in the eighteenth, nineteenth and first half of the twentieth century provides to the development of various aspects of their learning musical performers. To conclude, I return to the questions of basic research and its generating question. Finally, I joint some elements such as the way the sacred repertoire is performed by the ORB, the need to maintain a musical tradition - turning 300 years in 2013 - and the awareness of the importance of historical and social performance of these musicians and I explain how these factors have proved to be the main motivating factors for their musical practice, which consequently leads them to learn in a process of situated learning and thus construct their identities as musicians and citizens from São João del Rel.